The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21072440
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Endometriosis

Abstract: Endometriosis is one of the main common gynecological disorders, which is characterized by the presence of glands and stroma outside the uterine cavity. Some findings have highlighted the main role of inflammation in endometriosis by acting on proliferation, apoptosis and angiogenesis. Oxidative stress, an imbalance between reactive oxygen species and antioxidants, could have a key role in the initiation and progression of endometriosis by resulting in inflammatory responses in the peritoneal cavity. Neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 182 publications
(199 reference statements)
1
52
0
3
Order By: Relevance
“…Homeostasis maintenance of tissue is mainly regulated by cell death and some studies have shown that apoptosis increases during the menstrual cycle to retain cell homeostasis, removing aged cells from the functional layer of the endometrium [ 33 ]. The rate of apoptosis is decreased in endometrial cells of women with endometriosis, and therefore, it may contribute to the pathogenesis of the disease [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Homeostasis maintenance of tissue is mainly regulated by cell death and some studies have shown that apoptosis increases during the menstrual cycle to retain cell homeostasis, removing aged cells from the functional layer of the endometrium [ 33 ]. The rate of apoptosis is decreased in endometrial cells of women with endometriosis, and therefore, it may contribute to the pathogenesis of the disease [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin inhibited superoxide anion-induced overt pain-like behaviors, mechanical and thermal hyperalgesia and leukocyte recruitment in animal models through inhibition of MPO activity, oxidative stress, TNF-α and IL-1β production and NF-κB activation, and upregulation of IL-10, HO-1, and Nrf2 mRNA expression [89]. These evidences have highlighted the antioxidant, anti-inflammatory, and anti-angiogenic properties of curcumin in endometriosis therapeutics [90].…”
Section: Methodsmentioning
confidence: 99%
“…Curcumin (bis-α, β-unsaturated β-diketone) is a natural component which presents some therapeutically potential roles as anti-inflammatory guardian in the organism [17]. It can downregulate the expression of TNF-α, COX-2, IL-6 and TGF, TNF-α, IL-1, IL-6 and IL-8.…”
Section: Scientific Collection «Interconf» | № 49 481mentioning
confidence: 99%
“…Pathological lesions mostly occur in in the ovaries, fallopian tubes, the ligaments of the uterus, the urinary tract and the rectum. Intense pain, irregular uterine bleeding, dyspareunia are main symptoms which has a negative impact on mental and physical health [1]. Mental disturbances may express as a various form of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%